دور العناقيد الصناعية في إدارة مخاطر المؤسسات الصغيرة والمتوسطة - جبالي ،أسيا; بونقيب، أحمد (جامعة الوادي University of Eloued, 2025)
يتناول هذا المقال دور العناقيد الصناعية في إدارة مخاطر المؤسسات الصغيرة والمتوسطة، مع التركيز على دراسة حالة العنقود الرياضي سيالكوت بباكستان. ويهدف إلى تحليل كيفية إدارة المخاطر التي تواجهها المؤسسات الصغيرة والمتوسطة المكونة للعنقود الصناعي، وكيف يمكن للتنسيق والتعاون والتكامل الذي يستلزمه العنقود التقليل من هذه المخاطر. ولقد توصلت الدراسة إلى أن عنقود السيالكوت يواجه العديد من المخاطر: المخاطر القانونية، المخاطر الاقتصادية، المخاطر التنافسية ومخاطر سعر الصرف، وتتم إدارتها من خلال مجموعة من الطرق: كاختيار العنقود للبلدان ذات العملة المنخفضة، التدخل الحكومي، تعزيز العلاقة مع البنوك والمؤسسات المالية، واللجوء إلى الإبداع والابتكار في العنقود الصناعي من أجل زيادة وتحسين إنتاجيته والرفع من جودته. This article discusses the role of industrial clusters in managing the risks of small and medium enterprises, focusing on the case study of the Sialkot Sports Cluster in Pakistan. It aims to analyze how to manage the risks faced by small and medium enterprises that make up the industrial cluster, and how the coordination, cooperation and integration required by the cluster can reduce these risks. The study concluded that the Sialkot cluster faces several risks such as legal risks, economic risks, transportation and distribution risks, and technological risks, and they are managed through: adopting a market diversification strategy by diversifying the sources of raw materials needed for the production process by resorting to local production institutions and urging them to join the cluster to reduce costs on the one hand, and choosing countries with low currencies to address exchange rate risks on the other hand, government intervention, and resorting to creativity and innovation to raise the quality of the industrial cluster.
The role of industrial clusters in managing the risks of small and medium enterprises -Pakistan experience-
Keywords: العناقيد الصناعية; مخاطر المؤسسات الصغيرة والمتوسطة; التجربة الباكستانية.; Industrial clusters; SME risks; Pakistani experience.